Posouzení finanční situace podniku pomocí časových řad - Pšenčík, Jiří (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Tato bakalářská práce se zabývá finanční analýzou a zhodnocením situace společnosti PKD, s.r.o. v letech 2004 až 2008. Práce se skládá z praktické a teoretické části. V teoretické části jsou specifikovány použité ekonomické ukazatele a teoretické východiska. V praktické části se zaměřím na zhodnocení finanční situace pomocí finančních ukazatelů a jejich znázornění v časových řadách pomocí regresních křivek.

This thesis deals with financial analysis and evaluation of the situation of PKD, Ltd. between 2004 and 2008. Work consists of practical and theoretical parts. The theoretical parts are used in specified economic indicators and the theoretical basis of statistical analysis. The practical part will focus on the assessment of the financial situation with financial indicators and their representation in the time series by using regression curves.
An Examination of Financial Situation of the Company Using Time Series
Keywords: Ocelové konstrukce; Dačice; zámečnictví; finanční analýza; rentabilita; likvidita; rozvaha; časová řada; regrese; přímka; parabola.; Steel structures; Dacice; locksmithing; financial analysis; profitability; liquidity; balance sheet; time series; regression; straight line; parabola.